Phytochemical Investigation, Fatty Acid Analysis and In Vitro Membrane Stabilizing Activity of the Roots of Amaranthus spinosus L. (Dhaka University Journal of Science, 2021)
Ethylacetate extract of the roots of Amaranthus spinosus L. was subjected to phytochemical investigation and three compounds stigmasterol, 1-Eicosanol and oleic acid were isolated in pure state. The n-hexane extract was analysed for fatty acid with GC-FID and four saturated fatty acids; caprylic acid, stearic acid, arachidic acid and behenic acid, and four unsaturated fatty acids; palmitoleic acid, oleic acid, linoleic acid and erucic acid were identified and quantified. Different extracts were assessed to explore their in vitro membrane stabilizing activity using standard protocol. Methanol extract of A. spinosus showed 68.13% inhibition in hypotonic solution-induced hemolysis and 74.53% inhibition in heat induced hemolysis which was the highest than its other Kupchan fractions. Acetyl salicylic acid was used as standard that showed 42.00% inhibition of hemolysis at normal condition.Dhaka Univ. J. Sci. 69(1): 59-62, 2021 (January)